Mostra de Iniciação Científica 2015
DOI: 10.18226/35353535.v4.2015.112
|View full text |Cite
|
Sign up to set email alerts
|

Metodologia de Pesquisa de Dissertações sobre Inovação: Análise Bibliométrica

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Scientific research comprises an organized process that is based on experience, whose reliability of the results obtained comes from the efficiency of the methodology employed. (Bruchêz et al, 2018) As for its objectives, the research is identified as exploratory, since it is a study that, among its objectives, aims at increasing knowledge on a specific topic (Appoliário, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Scientific research comprises an organized process that is based on experience, whose reliability of the results obtained comes from the efficiency of the methodology employed. (Bruchêz et al, 2018) As for its objectives, the research is identified as exploratory, since it is a study that, among its objectives, aims at increasing knowledge on a specific topic (Appoliário, 2012).…”
Section: Methodsmentioning
confidence: 99%